2021
DOI: 10.1108/ijrdm-09-2020-0357
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how digital kiosk customer experience enhances shopping value, self-mental imagery and behavioral responses

Abstract: PurposeThis research analyzes how the dimensions of the customer experience derived from using a digital kiosk during the store visit influence shopping value, self-mental imagery and the behavioral intentions of buying and word of mouth. Mediation effects of utilitarian, hedonic and social shopping values are examined, as well as the mediating effect of self-mental imagery.Design/methodology/approachTwo empirical studies were conducted to test the research hypotheses. A first analysis was carried out using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…The 24-h chain convenient stores have become an important channel for buying daily necessities in Asia, as their density of distribution increases ( Chang et al, 2016 ; Kwak and Cho, 2019 ; Hsiao et al, 2020 ). In order to improve consumer experience and functionality of convenient stores, firms launched multiple media kiosks (MMKs) to expand their service scope ( Brengman et al, 2021 ; Lao et al, 2021 ). MMK is a self-server terminal that is commonly seen in the retail channel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 24-h chain convenient stores have become an important channel for buying daily necessities in Asia, as their density of distribution increases ( Chang et al, 2016 ; Kwak and Cho, 2019 ; Hsiao et al, 2020 ). In order to improve consumer experience and functionality of convenient stores, firms launched multiple media kiosks (MMKs) to expand their service scope ( Brengman et al, 2021 ; Lao et al, 2021 ). MMK is a self-server terminal that is commonly seen in the retail channel.…”
Section: Introductionmentioning
confidence: 99%
“…Self-service technology, which is self-server terminal, is simply a kind of intelligent human-computer interaction equipment, in which the user operates and completes the business through a device according to the provided instructions. This kind of self-server terminal not only makes extremely high profits for a retail store in the least space, but also allows consumers to have a delightful and novelty experience ( Ku and Chen, 2012 ; Grewal et al, 2020 ; Brengman et al, 2021 ; Lao et al, 2021 ), thus creating new added value for retailers ( Kwak and Cho, 2019 ). Although it is an interesting experience platform, firms are not suggested to focus only on MMKs, because MMKs increase the learning burden for consumers, especially the aged or children ( Chang et al, 2016 ; Hsiao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schlosser (2003) stated that a medium helps to induce more vividness in mental images. Lao et al (2021) found out that customer experience dimensions, that is, "sensorial, pragmatic, cognitive, and social," also have positive influence on the mental imagery. Huang and Ha (2021) found out that fluency in processing information and images enhances mental imagery.…”
Section: Discussionmentioning
confidence: 99%
“…Skard et al (2021) argued that the results support the notion that mental imagery "offers a sensory and emotional surrogate of consumption experience, it stands to reason that (it) may influence attitude strength enough affective response." Lao et al (2021) examined the effects of "sensorial, pragmatic, cognitive, and social" dimensions of customer experience on "shopping value, self-mental imagery, and behavioral intention." They also studied the mediating role of shopping values (hedonic, utilitarian, and social) and self-mental imagery between the customer experience and behavioral intentions (word of mouth and purchase intention).…”
Section: Literature Reviewmentioning
confidence: 99%